Pineapple plantlets ‘Vitória’ fertilized with potassium chloride and silicic acid: growth and nutritional composition - Paulo Cesar dos Santos (Revista Brasileira de Ciências Agrárias, 2017)
The objective of this study was to evaluate the effect of silicon and potassium fertilization on the growth and nutrient content of pineapple plantlets ‘Vitória’ obtained from in vitro cultivation. The experiment was conducted in a greenhouse from November 2013 to April 2014, totaling 150 days. The experimental design was randomized blocks, in a 4 x 2 factorial scheme, with four doses of potassium chloride (0, 1.25, 2.5 and 3.75 g L -1 ) with or without the application of silicic acid, with five replications of 12 plants each. The silicon concentration in pineapple plants ranged from 11.57 to 16.97 g kg -1 , and an increase of 33% in the nutrient levels in plants fertilized with the lowest dose of potassium chloride was observed. It was observed that increasing doses of potassium chloride together with silicic acid resulted in lower root volumes in pineapple plantlets. Potassium accumulation of pineapple plantlets fertilized with silicic acid was lower than that of non-fertilized plantlets.